Online training of communication in a non-native language for foreign students at the pre-university stage of training - Vasetska, L. I.; Solovyova, O. V.; Васецька, Лариса Іванівна; Соловйова, Ольга Володимирівна (My University, 2022)
The article analyzes the main problems in the online teaching of communication of a non-native language to foreign students at the pre-university stage of language training. The practical course "Ukrainian as a foreign language", which foreign students of the pre-university stage of training have, has its final goal to form a foreign language communicative competence. The online learning format requires finding new or improving traditional methods and forms of teaching a non-native language to foreigners.
Онлайн навчання спілкування нерідною мовою слухачів-іноземців довузівського етапу підготовки
Keywords: didactic principles; Ukrainian as a foreign language; communicative competence; on-line learning; digital educational materials